Quality testing at assessment of professional competencies in web learning management system - Nikitenko, Ye.V.; Trunova, O.V. (Математичні машини і системи, 2016)
The article offers ways to improve the quality of testing in the assessment of professional competence in Learning Management System, including the reviewed system architecture and algorithm of its work. The proposed module of checking the criterion validity tests based on the analysis of indicators of asymmetry, kurtosis and discrimination index, set of these characteristics indicates on the validation methods that can increase the quality of testing. Designed module of providing and assessment of tests based on fuzzy sets allows you assessing accurately at the testing and thus pursue integrated account both of quantitative and qualitative factors. У статті пропонуються шляхи підвищення якості тестування при оцінюванні рівня професійних компетенцій у веб-системі управління навчанням, зокрема, розглянуто архітектуру системи та алгоритм її роботи. Запропонований модуль перевірки критеріальної валідності тестів ґрунтується на аналізі показників асиметрії, ексцесу та індексу дискримінації; сукупність наведених характеристик вказує на способи валідизації, що дозволяє підвищити якість тестування. Розроблений модуль надання та оцінки тестів на основі нечітких множин надає можливість достатньо точно виставити оцінку при проходженні тестування і при цьому проводити інтегральний облік як кількісних, так і якісних факторів. В статье предлагаются пути повышения качества тестирования при оценке уровня профессиональных компетенций в веб-системе управления обучением, в частности, рассмотрены архитектура системы и алгоритм ее работы. Предложенный модуль проверки критериальной валидности тестов основывается на анализе показателей асимметрии, эксцесса и индекса дискриминации; совокупность приведенных характеристик указывает на способы валидизации, что позволяет повысить качество тестирования. Разработанный модуль предоставления и оценки тестов на основе нечетких множеств дает возможность достаточно точно выставить оценку при прохождении тестирования и при этом проводить интегральный учет как количественных, так и качественных факторов.